Review of Technical Education and Skills Development Authority (TESDA) scholarship programs in targeting the poor - Maribel Da\~no (Philippine Institute for Development Studies (PIDS), 2025)
This study examines how the Technical Education and Skills Development Authority (TESDA) scholarships effectively target the poor while achieving its internal and external efficiency outcomes. It defined "poor" in two ways: (1) individuals with income below USD 3 per day, based on the World Bank threshold; and (2) those with disadvantaged status according to TESDA's client classification, which includes 4Ps beneficiaries, rebel returnees, displaced persons, and other vulnerable groups. Two datasets were used for the analysis: the 2018-2022 Study on the Employment of TVET Graduates (SETG) from TESDA, and the TESDA Training Management Information System (T2MIS) data covering all TESDA scholars. The SETG dataset contains information on scholars versus non-scholars and includes income data for poor scholars, while the T2MIS dataset classifies scholars according to disadvantaged status. In addition, focus group discussions and interviews were conducted to enrich the analysis. One of the key findings is in surfacing the decline in targeting of disadvantaged scholars from 2018- 2022 and how scholar motivation and presence of TESDA regulations in training institutions impact the outcomes for the poor or disadvantaged scholars. Qualitative focus group discussion and interviews show that there is a need for a more reliable way to more accurately filter genuine poor scholars who will have the commitment to perform. The study contribute insights for TESDA allocation of scholarship budget on whether the regional needs and provincial poverty incidences are taken into account. Policy recommendations include requiring Technical Vocational Institutions (TVIs) to use national databases, such as the national ID system and other relevant data sources, to more effectively identify disadvantaged scholars. Additionally, the study recommends that scholar motivation be assessed during the selection process, as our results indicate that motivation significantly influences scholar performance.
Keywords: 330; TVET; scholarship; poor; skills; disadvantaged; linear probability model; propensity score matching